Anticancer potential and chemical profile of agarwood hydrosol - Mohamed Gameil, Abeir Hussein; Hashim, Yumi Zuhanis Has-Yun; Zainurin, Nur Aimi Aliah; Mohd Salleh, Hamzah; Syed Abdullah, Nadiah (UTM Press, 2019)
This is the first report discussing the chemical profile of agarwood hydrosol and its potential anticancer effects. Agarwood hydrosols, from two batches, obtained from Negeri Sembilan, Malaysia, were used in this study. Calu-3 cancer cells were used as a model cell line for lung cancer. The cells were cultured in Eagle’s minimum essential medium (EMEM) supplemented with 10% (v/v) fetal bovine serum (FBS). The study was carried out in two phases, namely the anticancer study via an attachment (AT) assay and cell viability (CV) assay, and then profiling the hydrosol from the two batches via GCMS and hSPME-GCMS. Design Expert software’s two-factor face-centered central composite design (FCCCD) was used to study the effects of agarwood hydrosol amount and time of exposure on cell attachment (AT) and viability (CV). The findings suggest that agarwood hydrosols of Aquilaria malaccensis possess both anti-attachment and cytotoxic effects on Calu-3 lung cancer cells. A linear model was developed for anti-attachment effects and a quadratic model for the cytotoxic effects with exposure duration being significant in both cases. From the profiling data, 1- tricosene and 16-hentriacontanone were identified as potential contributors to the anti-attachment and/or cytotoxic activity observed. In conclusion, agarwood hydrosol holds a potential to be further investigated as a source of anti-cancer compounds.